Consenso difuso, dissenso confuso: Paradoxos das políticas de inovaç\~ao no Brasil - Luiz Ricardo Cavalcante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– In this paper it is shown that the wide acknowledgement of the association between innovation and economic and social development as well as of the relevance of innovation policies formed a kind of misty consensus hardly contested in Brazil. However, the innovation policies adopted in the country lack an institutional framework to support their implementation marking what is called in this paper a messy dissensus. It is argued that the obstacles to the science, technology and innovation (ST&I) policies to contribute more effectively to Brazil increase its technological efforts have less to do with the innovation policies themselves and more to do with their detachment from the institutional framework used to implement them. It is shown that this institutional framework i) is barely adherent to the perception of a systemic nature of the innovation process; ii) does not create incentives to the bureaucrats and public institutions to allocate resources in the industrial sector; iii) encourages the pulverization of resources and the consequent loss of focus which may reduce the efficiency of the adopted policies; and iv) encourages the adoption of models and priorities established to contexts which are different from the Brazilian reality.
Keywords: O3; O33; O38; 330; science; technology and innovation (ST&I); innovation policies; linear model of innovation; systemic model of innovation; institutions